h-STABILITY AND BOUNDEDNESS IN THE PERTURBED FUNCTIONAL DIFFERENTIAL SYSTEMS - Goo, Yoon Hoe (Journal of the Chungcheong Mathematical Society, 2015)
In this paper, we investigate h-stability and bounds forsolutions of the the functional perturbed di®erential systems. KCI Citation Count: 0